2019
DOI: 10.1186/s12885-019-6329-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between hypoxia inducible factor 1 subunit alpha gene rs2057482 polymorphism and cancer risk: a meta-analysis

Abstract: Background: The rs2057482 polymorphism in the hypoxia inducible factor 1 subunit alpha (HIF1A) gene has been reported to be associated with a risk of several types of cancer, but this association has not yet been definitively confirmed. We performed this meta-analysis to determine whether rs2057482 is associated with overall cancer risk.Methods: The PubMed, Embase, and Web of Science databases were searched for the potential studies about the association between the rs2057482 and cancer risk. The data of genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The possible importance of variant alleles in rs11549465 with respect to RCC susceptibility was proposed in European patients [21]. Additionally, the meta-analysis by Wu et al (2019) performed on Asian population revealed that the polymorphism rs2057482 was associated with decreased overall cancer risk [55]. On the other hand, no significant differences between RCC cases and controls in genotype frequencies for rs11549465 and rs2057482 were observed in the Chinese population [22].…”
Section: Discussionmentioning
confidence: 99%
“…The possible importance of variant alleles in rs11549465 with respect to RCC susceptibility was proposed in European patients [21]. Additionally, the meta-analysis by Wu et al (2019) performed on Asian population revealed that the polymorphism rs2057482 was associated with decreased overall cancer risk [55]. On the other hand, no significant differences between RCC cases and controls in genotype frequencies for rs11549465 and rs2057482 were observed in the Chinese population [22].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic association of HIF1A with cancer risk has been universally confirmed over the past few years. 32 , 33 Guo et al have assessed the associations of three functional SNPs (rs2057482, rs1957757, and rs2301113) with clinicopathological parameters and prognosis of surgical HCC patients and found that HIF1A rs2057482 is significantly associated with clinical outcomes of Chinese HCC patients after surgery, especially in those with aggressive status. 34 In addition, functional assay indicated the potential effect of rs2057482 on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Renal fibrosis and cancer progression have been linked through several common pathomechanistic pathways including tissue hypoxia, inflammation and oxidative stress. Furthermore, there are several common mediators, such as transforming growth factor beta (TGF-beta)—a key driver of malignant transformation—as well as tissue fibrosis, the involvement of fibroblasts in fibrosis and in the tumor microenvironment, or hypoxia-inducible factor-1 (HIF-1) [ 2 , 3 , 4 , 5 ]. These factors (TGF-beta fibroblasts, HIF-1alpha) are the most important factors in wound healing and tissue repair; however, if they remain activated following healing of an acute injury such as hypoxia, they are the key factors of fibrosis progression.…”
Section: Mainmentioning
confidence: 99%